A New ZVT Two-Switch Forward Converter - Bakan, A. Faruk; Yavuzer, Caglar (IEEE, 2019)
This paper presents a new zero voltage transition two-switch forward converter. ZVT is achieved by using a snubber cell for each switch. The proposed snubber cell includes an auxiliary power switch, a capacitor, an inductor and two diodes. The operation principle of the snubber cell is explained in detail. Motivation of this study is reducing turn off losses and increasing switching frequency and thus increasing power density especially for high voltage and high power converters. Operation principles are explained in detail and simulation results are given for a two-switch converter used in a three-phase welding machine.
Keywords: two-switch forward converter; zero voltage switching; zero voltage transition; Engineering